Digital Storytelling In Teaching Writing at The Second Semester of Hamzawadi University - Nikmah, Wahida; Wati, Laila; Nazri, M. Adib; Prasetyaningrum, Ari (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this study was to determine the efficacy of utilizing Digital Storytelling as a method of instruction for writing during the second semester at Hamzanwadi University. This study utilised a pre-experimental design employing a one-group pre-test and post-test approach. The study sample comprised 30 students from the second semester 2D class. The data were gathered from students' pre-test and post-test through the administration of a writing assessment. Analysed data using SPSS 22 for Windows. Upon doing a paired sample t-test, it was determined that there was a substantial disparity in the primary score between the pre-test and post-test. The t-value (df=17) was -41.944, with a p-value of 0.000. Consequently, the alternative hypothesis was accepted, and the null hypothesis was rejected. Therefore, Digital Storytelling proved to be highly helpful in instructing writing throughout the second semester at Hamzanwadi University. Based on the methodology and findings of this study, the researcher recommends that English instructors incorporate this medium into their writing instruction.